PENGARUH PEMBERIAN PUPUK KANDANG SAPI DAN PUPUK ABG TERHADAP PERTUMBUHAN DAN PRODUKSI TIMUN (Cucumis sativus L.) - Darmawati J.S; Farida Hariani; Hendra Saputra (AGRIUM: Jurnal Ilmu Pertanian, 2013)
Research of the effect of cow manure and fertilizer on the growth and production ABG cucumber has been conducted on Tuar street, in the field trials of Agriculture  Faculty, University of Muhammadiyah Sumatera Utara street Tuar , District of Amplas  with altitude of 27 meters above sea level with a factorial randomized block design ( RAK - F ) with two treatment factors studied were Granting Manure factor ( K ) which consists of four levels, namely : K0 , K1 , K2 , K3 and Fertilizer factors Giving ABG ( A ) which consists of four levels, namely : A0 , A1 , A2 , A3 . Cow manure treatment showed significant effect on the length of the plant , harvest , fruit length , fruit diameter , fruit weight per plant but did not show a marked influence on the observation of the number of fruits per plant . ABG fertilizer treatment showed significant effect on the length of the plant , fruit length , fruit diameter , fruit weight per plant but showed no significant effect on harvest age and number of fruits per plant . Interaction between cow manure and fertilizer ABG showed a significant effect on plant length , fruit length , fruit diameter , fruit weight per plant , harvest , number of fruits per plant .Keywords : cow manure , fertilizer ABG , growth , production , cucumber